HUBUNGAN KEHAMILAN PADA USIA REMAJA DENGAN KEJADIAN PREMATURITAS, BERAT BAYI LAHIR RENDAH DAN ASFIKSIA - Latifah, Lutfatul; Anggraeni, Mekar Dwi (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2013)
ABSTRACT Pregnancy and labor in adolescent contribute to increase perinatal death in Indonesia. In adolescent pregnancy, complications such as preterm labor, low birth weight, and perinatal death often occur. The aim of this study to determine the association between adolescent pregnancy and preterm birth, low birth weight and asphyxia. Methods : All adolescent women who gave birth at Margono Soekarjo Purwokerto hospital in 2009 (n=60) were included in this population -based a survey of cohort retrospective study. Chi Square was used to analyse the relation between adolescent pregnancy and preterm birth, low birth weight and asphyxia. Result of this study shows the average age of adolescent mother were 17,8 years old, with deviation standard 1,038, youngest age was 14 and oldest was 19. Bivariate analysis shows there are significant relationship between adolescent pregnancy and preterm bith with p=0,012 and OR= 3,857, and between adolescent pregnancy and low birth weight with p=0,001 and OR=7. Meanwhile there is no relationship between adolescent pregnancy and asphyxia. Key words : adolescent pregnancy, preterm birth, low birth weight, asphyxia  Kesmasindo  Volume 6, ( 1) Januari 2013, Hal. 26-34